A novel lncRNA, TCONS_00006195, represses hepatocellular carcinoma progression by inhibiting enzymatic activity of ENO1. Issue 12 (December 2018) - Yu, Songman; Li, Ning; Huang, Zebing; Chen, Ruochan; Yi, Panpan; Kang, Rui; Tang, Daolin; Hu, Xingwang; Fan, Xuegong
Abstract Hepatocellular carcinoma (HCC) is one of the most common malignancies and has an unfavorable prognosis. The hepatitis B virus X (HBx) protein has been reported to be closely associated with hepatocarcinogenesis. Meanwhile, emerging evidence has indicated that long noncoding RNAs (lncRNAs) are involved in the pathogenesis and progression of cancers. Our previous investigation has demonstrated that HBx could promote HCC by regulating the expression levels of various lncRNAs. In this study, we identified an lncRNA, lncRNA-TCONS_00006195 (termed lncRNA-6195), which was downregulated in HBV-related HCC tissues compared with its expression in adjacent noncancerous hepatic tissues. Clinical data showed that a low level of lncRNA-6195 was correlated with a high Edmondson–Steiner grade of the tumor and a poor prognosis in HCC patients. Furthermore, lncRNA-6195 acted as a tumor repressor in the development of hepatitis B-related HCC, inhibiting HCC cell proliferation in vitro and in vivo. Moreover, lncRNA-6195 could combine with α-enolase (ENO1) and repress its enzymatic activity, thus further inhibiting the energy metabolism in HCC cells. Our results suggest that lncRNA-6195 represses the growth of HCC by inhibiting the enzymatic activity of ENO1. These findings provide new insights into the mechanisms underlying the lncRNA involvement in hepatocarcinogenesis and can serve as a basis for the development of novel strategies to hinder HCC.